The Place of Storytelling Research in English Language Teaching: The State of the Art - Daniel Ginting; Delli Sabudu; Yusawinur Barella; Ross Woods (VELES Voices of English Language Education Society, 2023)
Storytelling techniques serve as dynamic tools for enhancing language skills, encompassing both receptive (listening, reading) and productive (speaking, writing) proficiencies. In contrast to their non-narrative counterparts, these techniques offer a more potent array of teaching methodologies. This study aims to elucidate the current landscape of research concerning the efficacy of storytelling techniques. Initially, the investigation delves into the cognitive processing of narratives. Stories engage language processing centers, invigorate the visual cortex, evoke emotive responses, and facilitate comprehension of intricate information. Subsequently, the study explores linguistic processing theory and embodied cognition theory. Through an exhaustive literature review, this research applies a rigorous evidence synthesis method to assess selected studies, culminating in the amalgamation of findings when comparability permits. The study unveils that storytelling techniques foster reading and listening comprehension, bolster speaking and writing skills, and kindle creativity and imagination. Moreover, enhancements span vocabulary, grammar, and syntax. Nonetheless, while generally efficacious, the uniformity of effectiveness across diverse learners remains a nuanced aspect.